STUDI TENTANG SULAMAN BENANG EMAS MEMAKAI KACA DAN CERMIN PADA PELAMINAN DI DESA NARAS I KOTA PARIAMAN - Azka Hayati; Weni Nelmira (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
Gold thread embroidery using glass and mirrors is a cultural heritage that has been passed down from generation to generation, this craft can be found in the Naras I area (Kota Pariaman) which is the main producing area for aisles with superior quality gold thread and is in great demand by consumers in West Sumatra to other countries. neighbor. The purpose of the study was to describe the design of motifs, embroidery techniques and the meanings contained in gold thread embroidery using glass and mirrors on the aisle of Naras I. The method used was descriptive qualitative, with the types of primary data and secondary data used, data collection techniques through observation, questions and main problems, analysis technique is an interactive model related to the main problem, through data reduction, data presentation, and conclusion drawing. The results of the research are gold thread embroidery motifs found in several aisle products that use glass and mirrors such as tirai langik-langik, Dalamak, banta gadang and tabir, generally use naturalist plant motifs, namely (a) diamond flower, (b) sunflower (c) cornflower (d) kaluak paku and (e) kaluak randai, while the animal naturalist motif (a) peacock (b) butterfly, and geometric motifs in the form of monks. The technique of embroidery gold thread embroidery using glass and mirrors at Naras I started by using a special technique, namely the rajuik technique by attaching to the material by tying the glass in the form of a square tie and tying it diagonally and then arranging the gold thread with a balut glass stitch, the sewing thread that knitted the glass until the thread Sewing is invisible and neat. As well as the meaning that comes from the life of the people in Minangkabau in accordance with previous customs. The meaning of glass and mirror has the meaning of